Silicon expansion at the service of safety – A reversible potential-dependent switch for safer batteries. (December 2018) - Borenstein, Arie; Strauss, Volker; Yoonessi, Mitra; Kaner, Richard B.
Abstract: An intrinsic electrochemical potential-dependent safety switch has been designed to create safer lithium-ion batteries. This device takes advantage of the large volumetric change in silicon upon electrochemical reaction with Li ions at low potentials. This electrochemically-induced mechanical expansion disconnects the anode from the power source and prevents undesired and dangerous overcharging. This is the first time the well-studied silicon expansion is applied as a positive feature in favor of battery safety. The device response is ensured since it is located inside the cell as part of the anode, hence, too low potential, typically responsible for destructive overcharging automatically activates the protection mechanism. The potential at which the anode is "switched off" can be controlled by changing the dimensions of the silicon. The device is designed to fit into commercial battery cases. The safety switch successfully protected the anode at an applied abuse potential and showed reversibility, thus allowing the reuse of the battery after emergency shutdown. Highlights: Overcharging occurs at too low potentials applied on the anode and may result in dangerous consequences. Silicon dramatically changes its volume upon low potential. A new safety switch is suggested to prevent overcharging based on silicon volume change at these potential. The switch shutdown mechanism is reversible. The shutdown potential can be controlled by changing dimensions of the silicon in the switch.